2017
DOI: 10.1038/pr.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal human enteric neuronal progenitors can migrate, differentiate, and proliferate in embryonic and postnatal aganglionic gut environments

Abstract: BACKGROUNDEnteric neural stem/progenitor cells (ENSCs) offer an innovative approach to treating Hirschsprung disease (HSCR) and other enteric neuropathies. However, postnatal-derived human ENSCs have not been thoroughly characterized and their behavior in the embryonic and postnatal intestinal environment is unknown.METHODSENSCs were isolated from the intestines of 25 patients undergoing bowel resection, including 7 children with HSCR. Neuronal differentiation and proliferation of ENSCs from submucosal and mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…After cell culture, lentiviral labeling and transplantation to the distal colon, these cells were found to retain their capacity for self renewal and could be observed proliferating and differentiating into neurons within the aganglionic colon after 2 weeks in vivo. Indeed, the same research group has recently demonstrated that unsorted human ENSC harvested from postnatal ganglionated HSCR bowel resections can colonize both aneural chick gut and Ednrb −/− aganglionic colon both in ex vivo organotypic cultures and in vivo . Human ENSC were observed within the gut wall, close to the site of transplantation and gave rise to both neurons and glia.…”
Section: Transplantation Of Enteric Neural Stem Cells To Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…After cell culture, lentiviral labeling and transplantation to the distal colon, these cells were found to retain their capacity for self renewal and could be observed proliferating and differentiating into neurons within the aganglionic colon after 2 weeks in vivo. Indeed, the same research group has recently demonstrated that unsorted human ENSC harvested from postnatal ganglionated HSCR bowel resections can colonize both aneural chick gut and Ednrb −/− aganglionic colon both in ex vivo organotypic cultures and in vivo . Human ENSC were observed within the gut wall, close to the site of transplantation and gave rise to both neurons and glia.…”
Section: Transplantation Of Enteric Neural Stem Cells To Disease Modelsmentioning
confidence: 99%
“…Indeed, the same research group has recently demonstrated that unsorted human ENSC harvested from postnatal ganglionated HSCR bowel resections can colonize both aneural chick gut and Ednrb −/− aganglionic colon both in ex vivo organotypic cultures and in vivo. 49 Human ENSC were observed within the gut wall, close to the site of transplantation and gave rise to both neurons and glia. These studies taken together provide further evidence for potential autologous treatment of human neuropathologies.…”
Section: Tr An S Pl Antati On Of Enteri C Neur Al S Tem Cell S To Dmentioning
confidence: 99%
“…In cell culture experiments, both cell types form enteric neurospheres, which are also composed of neuronal, glial, fibroblast, immune, and smooth muscle cells in undefined combinations . However, so far little is known about the detailed cellular composition, the proportional distribution, and the interplay of the different cell types in enteric neurospheres …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stem cell therapy field may highly benefit from this approach. In previous studies, enteric neurospheres have been used to investigate their ENS restoration capacity for the development of novel stem cell therapies without addressing this aspect in detail …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation